Effective mineralization of anti-epilepsy drug carbamazepine in aqueous solution by simultaneously electro-generated H2O2/O3 process. (10th November 2018) - Yang, Bo; Wei, Tuo; Xiao, Ke; Deng, Jianping; Yu, Gang; Deng, Shubo; Li, Juying; Zhu, Caizhen; Duan, Huabo; Zhuo, Qiongfang
Abstract: A novel electro-generated hydroxyl radical (OH) technique was constructed to effectively degrade the anti-epilepsy carbamazepine (CBZ) representing typical recalcitrant pharmaceutical only through electrochemical method as an alterative peroxone process. The technique involves simultaneously electro-generated H2 O2 using a carbon-polytetrafluoroethylene (C/PTFE) cathode to reduce the injected O2 and electro-generated O3 using H2 O oxidation with a Ti mesh/PbO2 anode in membrane electrode assembly (MEA). The significant OH formation through the synergetic system of in-situ produced H2 O2 and O3 electrochemically could achieved carbamazepine decomposition and total organic carbon (TOC) removal as compared to electro-generated H2 O2 or O3 alone. The main influential factors including current density and aqueous pH were investigated to reveal their effect on CBZ removal efficiencies. Under optimal parameters, CBZ decomposition and TOC mineralization could be completely accomplished after 10 min and 90 min electrolysis, respectively. According to intermediates distribution (e.g. hydroxylated CBZ, phenolics, and carboxylic acids) identified by HPLC-MS/MS, the degradation pathways were proposed for CBZ removal by the synergetic system of C/PTFE-O2 and MEA. The above results indicated that this electrochemically synergetic system is a potential technique to further purify the water contaminated by recalcitrant pharmaceuticals. Graphical abstract: Highlights: A novel electrochemical advanced oxidation process was devised for water treatment. Dual-cell system was innovatively assembled to achieve electro-generated H2 O2 /O3 . Hydroxyl radicals can be effectively formed by the electrochemical peroxone process. The synergetic process could degrade ozone-refractory pharmaceutical contaminants. The degradation pathway of carbamazepine by the synergetic system was proposed.